Synthesis, Biological Evaluation and Docking Studies of 1,3,4-Oxadiazole Fused Benzothiazole Derivatives for Anticancer Drugs - Subramanyam, Madala; Sreenivasulu, Reddymasu; Gundla, Rambabu; Rao, Mandava V.B.; Rao, Koya P. (Letters in Drug Design & Discovery, 2018)
Background: Hetero atom containing compounds are well studied class of organic compounds exhibits variety of properties and applications. Design and synthesis of new heterocyclic compounds are always of great interest in synthetic and medicinal organic chemistry. Benzothiazole or 2-aminobenzothiazole scaffold based derivatives were reported to display a wide range of biological activities including anticancer, anti-tubercular, antiviral, fungicidal, etc. On the other hand, 1,3,4-oxadiazoles were permit to increase their biological activities due to H-bonding with receptors. These derivatives possess diverse biological activities which include anticancer, antiviral, antifungal, antibacterial and antidepressant etc. Due to interesting biological activity information of about these hetero cyclic moieties, benzothiazole/2-aminobenzothiazole and 1,3,4-oxadiazoles moieties, we chose to design a new series of heterocyclic compounds by mimicking these two types of scaffolds in a single molecule for our study. Methods: The 1,3,4-oxadiazole linked benzothiazole derivatives were synthesized by condensation of, 2-(4-(5-(benzo[d]thiazol-2-yl)-1,3,4-thiadiazol-2-yl)-2,6-dimethoxyphenoxy)acetohydrazide and POCl3 under reflux conditions. All these ten compounds structures were confirmed by spectral data 1H & 13C NMR, Mass, CHN analysis etc. Further, these compounds were evaluated for their anticancer activity against four human cancer cell lines, A549, MCF7, A375 and HT-29 in comparison to CA4 as a reference drug. We also carried out docking studies of these compounds in the Colchicines binding site of Tubulin (PDB_ID: 1SA0) using Glide docking tool indicated that the ligands show good interactions with active site residues. Results: A new series of 1,3,4-oxadiazole fused benzothiazole derivatives were synthesized successfully in totally six steps starting with 4-hydroxy-3,5-dimethoxybenzoyl chloride. All these newly synthesized compounds structures were confirmed by spectral studies and elemental analysis. As we designed for anticancer activity, they were assessed for their anticancer activity against four human cancer cell lines in comparison to a reference drug CA4. As expected, all the ten compounds exhibited anticancer activities against four cancer cell lines with half maximal inhibitory concentration (IC50) values ranging from 0.01 μM to 12.3 μM. The docking studies indicated all the compounds exhibited good binding energies with the receptor. Conclusion: In this study we designed a new series heterocyclic compounds by mimicking two types of scaffolds benzothiazole/2-aminobenzothiazole and 1,3,4-oxadiazoles moieties in a single molecule based on their biological activity in the literature. They were synthesized successfully and molecular structures were confirmed by spectral studies. As expected, all the compounds exhibited anticancer activities against four cancer cell lines. This study can provide a roadmap for design and synthesis of new drug molecules for antitumor and anticancer activity.
Keywords: Anticancer activity